Virtual Fatigue Behaviour Analysis of Coir Fibre-Reinforced PVC Composites - Gopalan Venkatachalam; Umapathy Jayanthi; Arumugasamy Suja; Senthil Gnanaaksaya; Sampath Aravindh; Pitchumani Shenbaga Velu; Kulendran Balamurugan; Rajendiran Gopal (International Journal of Polymer Science)
PVC (polyvinyl chloride) is a tough polymer used in applications, including plumbing and construction materials. As natural fibre-reinforced composites have more advantages over conventional synthetic composites, this paper focuses on the fatigue analysis of PVC composite which is reinforced with coir fibre. The influences of three input parameters, namely, the size of the coir fibre, coir fibre content, and the chemicals that are used in the treatment of coir fibre on the fatigue life of the composite are examined. In the response surface model (RSM), Box-Behnken designs (BBD) are employed for the preparation/analysis/optimization of the samples. ANSYS software is used to perform the fatigue analysis of different samples containing various combinations of the parameters. To determine the effects of various input parameters on the fatigue behaviour of composites, ANOVA is employed to determine their optimal levels. Regression equations are established to determine the fatigue limit. When treated with triethoxy(ethyl)silane, coir with a concentration of 6 wt.% and a particle size of 75 μm exhibits a maximum fatigue limit of 2.819 MPa.